Pengaruh Lingkungan Kerja Fisik, Disiplin Kerja, dan Kepemimpinan terhadap Kinerja Karyawan - Gunawan, I Made Arya; Wijaya, Putu Yudy; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
There is attention and findings regarding problems regarding the physical work environment, work discipline and leadership in an effort to improve and increase employee performance in accordance with the aim of this research to determine the influence of the physical work environment, work discipline and leadership on employee performance at PT. Balinese Car Creations. The population in this study was 62 employees at the company PT. Balinese Car Creations. Meanwhile, the number of samples in this research was 62 employees. The sampling technique in this research is using the saturated sampling method. The analysis technique used is Multiple Linear Regression Analysis. The research results show that the physical work environment, work discipline and leadership simultaneously have a positive and significant effect on employee performance at PT. Balinese Car Creations. This means that the better the work environment, work discipline and leadership, the more employee performance will increase. Suggestions that can be given to agencies include 1) It is hoped that every month the leadership will check the air conditioning and fans in each room so that they function optimally so that employees while working do not feel hot due to the lack of ventilation in the air circulation area. 2) Employees are expected to always be present on time according to working hours. 3) It is hoped that leaders will provide motivation to employees. 4) Leaders are expected to provide training to employees.